Impactos ambientais negativos provenientes do Urban Sprawl sobre a bacia hidrográfica do rio Gramame, no município de João Pessoa, PB, Brasil - Sousa, Cynthia Alves Félix de (2017)
The urbanization of cities and the intense transformations in intraurban space, both in the global sphere and in the national section, have been linked to environmental issues. As urbanization took place, there was a consequent and constant population and environmental impacts growth, and demands for habitation, infrastructures, distended growth of the urban network as well. At this conjuncture, the phenomenon called urban sprawl was considered to be linked to the urban environmental impacts diagnosed in numerous medium and large cities, often presenting a lack of adequate urban planning. In this perspective, the urbanization of João Pessoa, PB occurred in a fast and spread way, directed mainly to the borders of the southern region of the municipality, whose region is characterized chiefly by the great natural spaces, such as the Gramame River Basin. Thus, based on the assumption that urban sprawl may be harmful to the environment, this work aimed to investigate the associations between the urban environmental impacts diagnosed in the Gramame River Basin and the dispersed model of urbanization verified in the city. The methodology is a case study, being descriptive, with qualitative and quantitative analyzes, making it possible to observe the negative urban environmental impacts and their associations with the phenomenon of urban spreading. The results indicated negative urban environmental impacts such as water pollution by domestic effluents, devastation of the remaining vegetation, inappropriate disposal of solid urban waste, and erosion processes in soils throughout the area to be studied. The conclusion of this work is that the diagnosed impacts come mainly from conflicts of use and occupation of the soil, the lack of infrastructure of urban sanitation and deficiencies in the systems of inspection and environmental monitoring. The quantification of the impacts verified that the area to be studied is classified in a medium degree of environmental impacts. The most aggravating factors of these environmental impacts are the incidence of urban occupations gradually closer to sensitive natural spaces, and the lack of urban planning and infrastructure.